Synergistic Effects of Noni and Honey in Ameliorating Hyperglycemia and Oxidative Stress in Diabetic Rats - Fadlilah, Synta Haqqul; Pauzi, Rizqi Yanuar; Muntafiah, Alfi; Silva, Ghea De (Journal of Biomedicine and Translational Research, 2026)
Background: The global prevalence of type 2 diabetes mellitus (T2DM) continues to rise, posing significant health challenges. T2DM is characterized by insulin resistance and often leads to hyperglycemia and oxidative stress, which increase the risk of complications. Natural products like noni (Morinda citrifolia) and honey have been studied individually for their antidiabetic properties.Objective: This study investigates the combination of noni and honey to regulate blood glucose, improve insulin sensitivity, and enhance antioxidant activity in diabetic models..Methods: The study involved 35 male Wistar rats divided into seven groups, including healthy controls, diabetic controls, and various treatment groups receiving noni fruit juice, honey, or their combinations at different dosages. Type 2 diabetes was induced using streptozotocin-nicotinamide (STZ-NA). Treatments of Noni and Honey were administered via gavage every day for 28 days. Blood glucose and SOD levels were measured using enzymatic assay methods, whereas insulin concentrations were determined through ELISA (Enzyme-Linked Immunosorbent Assay).Results: The combination of noni and honey significantly reduced fasting blood glucose levels (p < 0.0001), with the highest reduction observed in the MCH3 group. Insulin levels and HOMA-B were significantly increased, while HOMA-IR was decreased in treatment groups, particularly in MCH3. SOD activity was notably enhanced, indicating improved antioxidant status.Conclusion: The combination of noni fruit juice and honey exhibits synergistic hypoglycemic and antioxidant effects in diabetic rats, with the highest dose (MCH3) showing the most significant therapeutic potential. These findings support the potential use of noni and honey as complementary treatments in managing type 2 diabetes and its associated metabolic complications.